Boys in the valley - Fracassi, Philip, 1970- (Nightfire, Tor Publishing Group, 2023)
"St. Vincent's Orphanage for Boys. Turn of the century, in a remote valley in Pennsylvania. Here, under the watchful eyes of several priests, thirty boys work, learn, and worship. Peter Barlow, orphaned as a child by a gruesome murder, has made a new life here. As he approaches adulthood, he has friends, a future...a family. Then, late one stormy night, a group of men arrive at their door, one of whom is badly wounded, occult symbols carved into his flesh. His death releases an ancient evil that spreads like sickness, infecting St. Vincent's and the children within. Soon, boys begin acting differently, forming groups. Taking sides. Others turn up dead. Now Peter and those dear to him must choose sides of their own, each of them knowing their lives - and perhaps their eternal souls - are at risk"--